Любимая девочка дяди Федора - Успенский Эдуард Николаевич (Самовар, 2000)
Экземпляры: ф.3 (20180409) / Инвентарный номер: 36110 / Цена: 28.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: У 77 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6